2014
DOI: 10.1038/clpt.2014.144
|View full text |Cite
|
Sign up to set email alerts
|

Adjusted Indirect Treatment Comparison of the Bioavailability of WHO-Prequalified First-Line Generic Antituberculosis Medicines

Abstract: Approval of generic medicines is based on bioequivalence with the innovator product, but it is not unusual for generics to be interchanged with each other. This study investigated the differences in bioavailability between World Health Organization-prequalified antituberculosis generics by means of indirect comparisons to ensure interchangeability between these diverse generics. Data on 22 products containing isoniazid, rifampicin, pyrazinamide, or ethambutol in single- or fixed-dose combination were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Products meeting the proposed acceptance criteria can be interchanged as necessary with little concern regarding possible shifts in the quality of therapy as observed by the patient or treating professional. As suggested previously [9], this work indicates that the best way to gain greater assurance of generic interchangeability, when necessary, is to place a constraint on the point estimates in the original generic vs. reference product bioequivalence studies.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Products meeting the proposed acceptance criteria can be interchanged as necessary with little concern regarding possible shifts in the quality of therapy as observed by the patient or treating professional. As suggested previously [9], this work indicates that the best way to gain greater assurance of generic interchangeability, when necessary, is to place a constraint on the point estimates in the original generic vs. reference product bioequivalence studies.…”
Section: Discussionmentioning
confidence: 60%
“…This was observed in Gwaza et al [9] by comparing a diverse group of prequalified firstline tuberculosis (TB) medicines in order to explore the utility of the recommended approach for conducting adjusted indirect comparisons. On one hand, the study found that the TB products being compared could be interchanged as necessary without significant concern regarding possible shifts in the quality of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…AICs have been adopted as a useful tool for assessing bioequivalence between generic products and their switchability, as well as for comparing originator products from different markets that have previously been shown to be bioequivalent with the same generic product . To our knowledge, this is the first study to compare clopidogrel generic products.…”
Section: Discussionmentioning
confidence: 99%
“…Clopidogrel generic products were compared using the method of AICs that uses the results from the individual bioequivalence studies for each generic product vs the reference product. The comparison is performed between the pairs of generic products in relative terms since the reference represents the 100% value in all bioequivalence studies, which adjusts the study results . In this study, for each pair of generic products, adjusted indirect comparison is performed in 1 direction, e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation